2010
DOI: 10.1212/wnl.0b013e3181cf6ec0
|View full text |Cite
|
Sign up to set email alerts
|

The rising prevalence and changing age distribution of multiple sclerosis in Manitoba

Abstract: The prevalence of multiple sclerosis (MS) in Manitoba is among the highest in the world. The rising prevalence with minimally changing incidence suggests improving survival. This study supports the use of administrative data to develop case definitions and further define the epidemiology of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
278
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(309 citation statements)
references
References 27 publications
23
278
1
7
Order By: Relevance
“…The effects of this assumption are likely to be small, given that most MS cases are diagnosed at age 20 years and older. The model shows peak incidence occurring at a later age than other Canadian studies undertaken in Nova Scotia 21 and Manitoba; 22 however, the overall incidence rates produced by the model were similar to these earlier studies.…”
Section: Strengths and Limitationssupporting
confidence: 71%
See 2 more Smart Citations
“…The effects of this assumption are likely to be small, given that most MS cases are diagnosed at age 20 years and older. The model shows peak incidence occurring at a later age than other Canadian studies undertaken in Nova Scotia 21 and Manitoba; 22 however, the overall incidence rates produced by the model were similar to these earlier studies.…”
Section: Strengths and Limitationssupporting
confidence: 71%
“…22 We generated prevalent MS actors in two steps. First, we applied empirical estimates of sex-and age-specific MS incidence rates to the model's synthetic Canadian population for each year, both historical and projected.…”
Section: Ms Status: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…7 One study examining hospital stays in newborns of mothers with MS 11 reported longer stays (relative risk 5 1.5; 95% CI: 0.99-2.3) compared with newborns of mothers without MS 11 ; however, the authors speculated this was attributable to the common practice of discharging mother and newborn home together, as no other adverse birth outcomes were observed. Our study differed from previous studies 4,11 examining birth hospitalizations in a number of ways: first, our study included a cohort of women with clinically definite MS confirmed by an MS specialist neurologist, rather than relying on a single ICD code (a valid algorithm for MS requires multiple ICD billing codes recorded over a period of time) 23 to identify MS. Second, we found that the length of birth hospitalization in patients with MS was not associated with disease duration or level of disability, which was not previously examined. These findings should be considered exploratory in nature and require confirmation.…”
mentioning
confidence: 99%
“…Older people with MS constitute a growing proportion of the MS population 53 ; however, little is known about aging with MS or factors that affect successful aging with MS. In order to describe healthy aging from the perspective of the older person with MS, researchers interviewed 18 people who were 55 years of age and older with symptoms for 20 or more years.…”
Section: Research On Aging and Older Adults With Multiple Sclerosismentioning
confidence: 99%